Controlling Biofouling in Seawater Reverse Osmosis Membrane Systems - Dhakal, Nirajan (Netherlands : CRC Press, 2018)
"The increasing global demand for potable water and the economy of scale in desalinating water will increase large-scale Sea Water Reverse Osmosis (SWRO) plants in future. However, organic/biological fouling in SWRO membranes caused due to seasonal proliferation of algae and algal released organic matter (AOM) is an issue for cost effective operation of SWRO plants. In order to maintain the stable operation of SWRO plants, reliable pre-treatment systems which substantially reduces AOM and nutrients, such as carbon and phosphate from SWRO feed water, are needed. Hence, this research (i) developed a bacterial regrowth potential (BRP) method to assess the biofouling potential of SWRO feed water; and (ii) investigated the nutrients removal and the delay in biofouling when tight ultrafiltration (10 kDa) and bio-based phosphate adsorbent are used as pre-treatment systems. BRP method was developed using a natural consortium of marine bacteria as inoculum and flow cytometry. Experimental studies revealed that tight UF reduced AOM, bio-based phosphate adsorbent reduced phosphate, which lead to the lower biofouling potential of SWRO feed water. Simulation of biofouling in SWRO using membrane-fouling simulator (MFS) shows that the pre-treated feed water using the aforementioned pre-treatment systems will lead to less biofouling due to lower rate of head loss development. It is expected that the BRP method developed through this research and the tested pretreatment systems will result in better operation and maintenance of SWRO plants during algal blooms."--Provided by publisher.
chapter 1 General introduction / Nirajan Dhakal -- chapter 2 Perspectives and challenges for desalination / Nirajan Dhakal -- chapter 3 Measuring bacterial regrowth potential (BRP) in seawater reverse osmosis using a natural bacterial consortium and flow cytometry (FCM) / Nirajan Dhakal -- chapter 4 Fouling of ultrafiltration membranes by organic matter generated by four marine algal species / Nirajan Dhakal -- chapter 5 The role of tight ultrafiltration on reducing fouling potential of SWRO feed water / Nirajan Dhakal -- chapter 6 Phosphate removal in seawater reverse osmosis feed water: An option to control biofouling / Nirajan Dhakal -- chapter 7 Conclusions and outlook / Nirajan Dhakal.
Submitted in fulfillment of the requirements of the Board of Doctorates of Delft University of Technology and of the Academic Board of the UNESCO-IHE Institute for Water Education for the Degree of Doctor to be defended in public on Thursday 30 November 2017 at 15:00 hours in Delft, the Netherlands.
Keywords: Fouling; Saline water conversion -- Reverse osmosis process